Dietary Phaseolus vulgaris extract alleviated diet-induced obesity, insulin resistance and hepatic steatosis and alters gut microbiota composition in mice. (January 2016) - Song, Haizhao; Han, Wen; Yan, Fujie; Xu, Dongdong; Chu, Qiang; Zheng, Xiaodong
Highlights: Phaseolus vulgaris extract administration reduced diet-induced body weight gain. Phaseolus vulgaris extract administration attenuated diet-induced hepatic steatosis. Phaseolus vulgaris extract improved glucose intolerance and insulin resistance. Phaseolus vulgaris extract administration modified the composition gut microbiota. Abstract: Phaseolus vulgaris may reduce appetite, body weight and gut microbiota and has been shown to contribute to the development of obesity, type 2 diabetes and non-alcoholic fatty liver disease. This study was conducted to investigate the impact of P. vulgaris extract (PVE) on obesity and obesity-associated metabolic syndromes, and determine whether the protective effects of PVE were associated with modulation of gut microbiota. C57BL/6J mice were fed low-fat diet, high-fat diet or high-fat diet supplemented with PVE of 50 mg/kg. The composition of gut microbiota was analysed by 16S rDNA sequencing. Our results showed that PVE treatment reduced body weight and improved hepatic steatosis and insulin resistance in high-fat diet-fed mice. PVE administration increased the relative abundance of Bifidobacterium, Lactobacillus and Akkermansia at the genus level. In conclusion, PVE protects from diet-induced obesity, insulin resistance and hepatic steatosis, and these beneficial effects were associated with the PVE-related modulation of gut microbiota.